Is Time of the Essence: A Retrospective Analysis of Operating Room Procedure Length for First Phase Damage Control Trauma Surgery - Smith, Alison; Hakki, Lynn; Friedman, Jessica; Schroll, Rebecca; Guidry, Chrissy; McGrew, Patrick; Tatum, Danielle; Duchesne, Juan (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Background: Damage control surgery (DCS) involves limiting operating room (OR) time for patients with multiple life-threatening injuries and coagulopathy who are reaching physiologic exhaustion. However, there is a paucity of current evidence to support a survival benefit with shorter OR times. The objective of this study was to determine if operation length affects mortality in trauma patients with abdominal injuries. Methods: An 8-year retrospective review of adult patients with DCS for penetrating abdominal trauma at a Level I trauma center was conducted. Univariate and multivariate analyses were performed. Results: Patients were stratified into short OR group (SHORT, n = 95) and long OR group (LORT, n = 98) based on the median operative time of 157 minutes. The SHORT group received more ICU blood transfusions (52.6% vs. 35.7%, p = 0.02). Average hospital length of stay (22.8 + 2.3 vs. 31.0 + 3.5 days, p = 0.05) and ICU length of stay (10.6 + 1.2 vs. 12.6 + 1.4 days, p = 0.28) were lower in the LORT group. The SHORT group had 22 patients with an unexpected return to the OR versus 3 in the LORT group (p < 0.0001). OR time was not an independent risk factor for mortality (odds ratio 1.0, 95% CI 0.98–1.0, p = 0.48). Conclusions: Modern damage control practices should focus on early surgical control in combination with effective intra-op resuscitation efforts and not on the amount of time required to accomplish these resuscitative goals. These findings suggest that in the era of modern DCS, the old tenet of 60 minutes may not be as relevant.